Transdermal theranostics. Issue 2 (29th May 2020) - Than, Aung; Zan, Ping; Chen, Peng
Abstract: Skin offers an easily accessible site for drug administration as well as for health signal monitoring, with non‐invasiveness or minimal‐invasiveness, convenience, and good patient compliance. Transdermal theranostics promises for personalized, home‐based, and long‐term management of chronic diseases, and is expected to change the landscape of healthcare profoundly. In this article, we review the recent advances in transdermal drug delivery, diagnosis based on sweat and skin interstitial fluid, and wearable devices. The advantages, limitations, and commercialization of these emerging techniques are comparatively discussed. Abstract : Skin offers an easily accessible site for drug administration as well as for health signal monitoring, with non‐invasiveness or minimal‐invasiveness, convenience, and good patient compliance. Transdermal theranostics promises for personalized, home‐based, long‐term management of chronic diseases.